Epidemiological Analysis Of Occupational Health Risks In Shallot Threshing Activities Using Job Safety Analysis (HEALTH CARE: JURNAL KESEHATAN, 2026)
Background: Shallot perontokan, namely the manual separation of shallot bulbs from leaves or stalks after harvest, is a repetitive agricultural activity that may expose workers to ergonomic, biological, mechanical, heat-related, and environmental hazards. Aim: This study aimed to identify occupational safety and health hazards, risks, and control measures in shallot perontokan work using Job Safety Analysis. Methods: A descriptive qualitative document-based analysis was conducted using a JSA workbook for perontokan work in a shallot farming area. The instrument contained work processes, H/S/E classification, hazards, risks, control measures, and control-verification columns. Results: The JSA identified 12 sequential work processes. Six processes were categorized as H/S/E and six as H/S. Major hazards included poor work preparation, unsuitable personal protective equipment, heavy loads, awkward posture, repetitive hand movements, sharp cutting tools, rotten shallots, dust, microorganisms, heat exposure, slippery routes, and scattered tools. All 12 control-verification rows were marked “No”, indicating that the proposed controls required supervisor verification before work execution. Conclusion: Shallot perontokan should be managed as a structured occupational safety activity. JSA provides a practical basis for developing contextual agricultural standard operating procedures, strengthening worker briefing, improving ergonomic control, ensuring personal protective equipment use, and preventing repeated hazards in post-harvest shallot handling.